The role of micro-implant-assisted rapid palatal expansion (MARPE) in clinical orthodontics - a literature review - Chuang Yun-Hsuan; Chen Jen-Hsuan; Ho Kwok-Hing; Wang Kai-Long; Hsieh Shun-Chu; Chang Heng-Ming (Sciendo, 2021)
A maxillary transverse deficiency is a common craniofacial problem. Rapid palatal expansion (RPE) has been traditionally considered for the treatment of children and young adolescents, but this is not applicable in late adolescents or adults due to the ossification of facial sutures. A surgically assisted rapid palatal expansion (SARPE) was initially advocated for this group of patients, but the surgical procedure is associated with morbidity. As temporary anchorage devices (TADs) have been recently and popularly applied in clinical orthodontics, micro-implant-assisted rapid palatal expansion (MARPE) has been employed to facilitate maxillary expansion in skeletally mature patients. There have been various proposed MARPE designs and the outcomes appear promising. The aim of the present article is to discuss the role of MARPE in clinical orthodontics by reviewing its background, design, indications, treatment effects, stability, and limitations in the current literature. The treatment effects of two types of MARPE, bone-borne and tooth-bone-borne (hybrid), will be individually assessed.